2022
DOI: 10.1186/s12902-022-01059-7
|View full text |Cite
|
Sign up to set email alerts
|

Primary hyperparathyroidism in Saudi Arabia revisited: a multi-centre observational study

Abstract: Purpose Primary hyperparathyroidism (PHPT) is a common cause of hypercalcemia and remains understudied within the Arabian population. The present study, the largest of its kind within the Gulf Cooperation Council (GCC) countries, aims to determine the demographics and clinical presentation of PHPT in Saudi Arabia. Methods In this multi-center retrospective study involving three tertiary hospitals in different geographic locations of Saudi Arabia na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…As reported in other studies (16, [20][21][22], nephrolithiasis was the most common presenting feature; the prevalence of osteoporosis was lower compared with studies reporting similar rates of symptomatic PHPT (5,6,16,21,22) and may be explained by less frequent screening for hypercalcaemia at primary levels of care.…”
Section: Discussionmentioning
confidence: 46%
“…As reported in other studies (16, [20][21][22], nephrolithiasis was the most common presenting feature; the prevalence of osteoporosis was lower compared with studies reporting similar rates of symptomatic PHPT (5,6,16,21,22) and may be explained by less frequent screening for hypercalcaemia at primary levels of care.…”
Section: Discussionmentioning
confidence: 46%
“…As reported in other studies [ 16 , 20 22 ], nephrolithiasis was the most common presenting feature; the prevalence of osteoporosis was lower compared with studies reporting similar rates of symptomatic PHPT [ 5 , 6 , 16 , 21 , 22 ] and may be explained by less frequent screening for hypercalcaemia at primary levels of care.…”
Section: Discussionmentioning
confidence: 59%
“…The average age of presentation in the current study was 42 years. Two recent studies from Asia have reported a mean age of 56 and 59 years [ 10 , 11 ]. Our patients continue to be much younger than patients from developed countries and other Asian countries [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the relatively low prevalence of abnormalities detected in routine X-rays, bone densitometry by DEXA revealed osteoporosis in over one-third of the patients, highlighting the detrimental skeletal effects of PHPT. Two recent studies from Asia have documented osteoporosis in 32.7% and 50% of patients [ 10 , 11 ]. Commonly reported gastrointestinal manifestations are recurrent pain in the abdomen, constipation, heartburn, nausea, and anorexia, which occur in about 45%, 33%, 30%, 20%, and 15% of cases, respectively [ 21 ].…”
Section: Discussionmentioning
confidence: 99%